“Teachers and deaf university students’ experiences” - Proaño León, Shirley Vanessa (2024)
This research study reports the perspective on the experiences of the teachers and the deaf student in a university career. The main objective is to analyze the experiences of teachers and a deaf university student in the teaching-learning process in the career of Pedagogy of National and Foreign Languages in the sixth semester of the Technical University of Cotopaxi in 2023-2024. This study has a qualitative approach. Three interviews were used to obtain data. The first was the teachers’ interview adapted from Sultanbeova (2019). In addition, the second was the deaf student’s interview and the third was the interpreter’s interview adapted from Mazoue (2011). The population was 4 teachers, 1 deaf university student, and 1 interpreter. They were at the sixth level in the Pedagogy of National and Foreign career at the Technical University of Cotopaxi. This was selected by “Sampling method”. The results showed that teachers have challenges because they do not know sign language and have no experience with deaf students. Another difficulty was because the deaf student had a low level of English complicating the teaching-learning process. On the other hand, the deaf student was very motivated to continue learning and finish her career because some of the professors effectively taught her and the deaf student had the help of an interpreter at all times. This made her feel accepted by her teachers and classmates.